1999
DOI: 10.1074/jbc.274.53.38004
|View full text |Cite
|
Sign up to set email alerts
|

The Human and Mouse GATA-6 Genes Utilize Two Promoters and Two Initiation Codons

Abstract: GATA-6 has been implicated in the regulation of myocardial differentiation during cardiogenesis. To determine how its expression is controlled, we have characterized the human and mouse genes. We have mapped their transcriptional start sites and demonstrate that two alternative promoters and 5 noncoding exons are utilized. Both transcript isoforms are expressed in the same tissue-specific and developmental stage-specific pattern, and their ratio appears similar wherever examined. The more upstream noncoding ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 52 publications
6
67
0
Order By: Relevance
“…All three factors were efficiently synthesized in explants (Fig. 6A), including both the short and the long isoforms of GATA6 that have previously been characterized (Brewer et al, 1999;Peterkin et al, 2003). We observed that approximately equivalent amounts of different GATA proteins are synthesized; yet we observe consistent differences in the induction of cardiogenic gene expression (Fig.…”
Section: Developmental Dynamicssupporting
confidence: 66%
See 1 more Smart Citation
“…All three factors were efficiently synthesized in explants (Fig. 6A), including both the short and the long isoforms of GATA6 that have previously been characterized (Brewer et al, 1999;Peterkin et al, 2003). We observed that approximately equivalent amounts of different GATA proteins are synthesized; yet we observe consistent differences in the induction of cardiogenic gene expression (Fig.…”
Section: Developmental Dynamicssupporting
confidence: 66%
“…Whatever the molecular mechanism involved in mediating these different functions of GATA factors, this will probably involve differences in the co-factors that associate with each GATA transcription factor, subtle differences in their DNA-binding site preferences (Sakai et al, 1998), and additional mechanisms connected to the N-terminal protein domain that is present in GATA6, but not in GATA4 and 5 (Brewer et al, 1999). The crucial role of GATA4 in mammalian cardiogenesis has been highlighted in recent studies.…”
Section: Differential Requirements For Gata Factors Are Mediated By Nmentioning
confidence: 99%
“…We did not find any Gata5-like ESTs and only three tGata4 ESTs, all of which encoded partial clones. Focussing on one of the tGata6 clones, we found that tGata6 uses an alternative upstream ATG like mouse and human GATA6, which has not been reported in the laevis Gata6 cDNAs (Brewer et al, 1999). In laevis, a downstream, internal ATG is assumed to be used; therefore, the tGata6 has a longer open reading frame than the laevis Gata6 cDNAs.…”
Section: Gata6mentioning
confidence: 70%
“…b tropicalis gata6 appears to use an alternative upstream ATG like mouse and human, the reported laevis cDNAs do not contain these sequences; therefore, it is assumed that the downstream ATG is used (Brewer et al, 1999).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…In mouse embryos, GATA6 gene is expressed in the precardiac mesoderm, heart tube, atria and ventricles [7,9]. GATA6 plays an important role in endocardial cushion formation and outflow tract morphogenesis [10].…”
Section: Introductionmentioning
confidence: 99%